Breakout nations In pursuit of the next economic miracles - Ruchir Sharma (RSA, London Blackstone Audiobooks, 2012)
After a decade of rapid growth, the world's most celebrated emerging markets are poised to slow down. Which countries will rise to challenge them?
Keywords: Economic forecasting